The role of epigenetic modifications in sensory hair cell development, survival, and regulation - Xiao, Ying; Li, Dan (Frontiers in Cellular Neuroscience, 2023)
The cochlea is the sensory organ in the periphery, and hair cells are its main sensory cells. The development and survival of hair cells are highly controlled processes. When cells face intracellular and environmental stimuli, epigenetic regulation controls the structure and function of the genome in response to different cell fates. During sensory hair cell development, different histone modifications can induce normal numbers of functional hair cells to generate. When individuals are exposed to environmental-related hair cell damage, epigenetic modification also plays a significant role in the regulation of hair cell fate. Since mammalian hair cells cannot regenerate, their loss can cause permanent sensorineural hearing loss. Many breakthroughs have been achieved in recent years in understanding the signaling pathways that determine hair cell regeneration, and it is fascinating to note that epigenetic regulation plays a significant role in hair cell regeneration. In this review, we discuss the role of epigenetics in inner ear cell development, survival and regeneration and the significant impact on hearing protection.